2012
DOI: 10.1016/j.jclinepi.2011.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Two methods provide similar signals for the need to update systematic reviews

Abstract: Objective Apply and compare two methods that identify signals for the need to update systematic reviews, using three Evidence-based Practice Center reports on omega-3 fatty acids as test cases. Study Design and Setting We applied the RAND method, which uses domain (subject matter) expert guidance, and a modified Ottawa method, which uses quantitative and qualitative signals. For both methods, we conducted focused electronic literature searches of recent studies using the key terms from the original reports. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 12 publications
0
42
0
Order By: Relevance
“…[13][14][15] We suggest that review authors consider SOE domains approach in synthesis. Using SOE domains as a framework, authors would consider if any new primary studies identified would change the judgments about SOE domains (i.e., study limitations, consistency, precision, directness, and reporting bias).…”
Section: Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] We suggest that review authors consider SOE domains approach in synthesis. Using SOE domains as a framework, authors would consider if any new primary studies identified would change the judgments about SOE domains (i.e., study limitations, consistency, precision, directness, and reporting bias).…”
Section: Recommendationmentioning
confidence: 99%
“…However, the process for how to determine if there is sufficient evidence to change a prior grade is an open question. As described above, recent EPC work has addressed when to update a review [13][14][15] and an EPC Workgroup is currently seeking to determine the predictive validity of SOE grading. In general, the judgment is whether enough new evidence exists to change the conclusions or confidence in conclusions.…”
Section: Summarizing and Assessing Body Of Evidencementioning
confidence: 99%
“…Most KIs noted that the tools to assess the RB of existing systematic reviews were not appropriate to determine whether the RB of individual studies can be used in the current review. [1][2][3][4][11][12][13][14][15] The most important criterion, according to the KIs, is the type of tool used to evaluate the RB and transparency of the study description. Reviews from presumably reliable sources, such as The Cochrane Collaboration (EPC Program), were preferred.…”
Section: Assessment Of the Risk Of Biasmentioning
confidence: 99%
“…Reviews from presumably reliable sources, such as The Cochrane Collaboration (EPC Program), were preferred. [1][2][3][4][11][12][13][14][15] The KIs agreed that an existing review should not necessarily use the same tool to evaluate the RB that would be used in the current review, but the evaluation of the former needs to be performed with an accepted and appropriate tool. In addition, the tools to evaluate the RB should be cited in the study methods.…”
Section: Assessment Of the Risk Of Biasmentioning
confidence: 99%
See 1 more Smart Citation